USM, NCIA COLLABORATES TO SET UP COMMUNITY INNOVATION CENTRE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PUTRAJAYA, July 2015 Universiti Sains Malaysia (USM) will help to boost the momentum of economic growth and development in the Northern Corridor Economic Region (NCER) by collaborating with the Northern Corridor Implementation Authority (NCIA) to establish a Community Innovation Centre (CIC).